AN ANALYSIS OF STUDENTS’ ERRORS IN CHANGING ACTIVE VOICE TO PASSIVE VOICE: A CASE OF THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 1 GUBUG IN ACADEMIC YEAR 2023/2024 - Emy Nurussa’adah; Siti Lestari; Maria Yosephin (CV. Mitkom Indotama, 2024)
This study aims to determine the types of error that are made by the students in changing active voice to passive in simple present tense and simple past tense, and the factors that cause the students make errors in changing active voice to passive voice in simple present tense and simple past tense. The method used in this study was qualitative method. The subject of this study was XI-1 class of SMA Negeri 1 Gubug. The researchers took 30 students as the sample. The data was collected through observation, test and questionnaire. The result of the error analysis showed that the students made errors into four types, those were omission (103 errors or 13.8%), addition (65 errors or 8.7%), misformation (510 errors or 68.4%) and misordering (68 errors or 9.1%). According to the Brown’s theory and the finding of this study, the researchers found that the factors causing the students made errors were classified as intralingual transfer, interlingual transfer, context of learning and communication strategies